The 10th International Conference on Advanced Materials and Systems (ICAMS 2024) (Sciendo, 2024)
The 10th International Conference on Advanced Materials and Systems (ICAMS 2024) will be held in the South-Eastern region of Europe and is focused on the field of Materials Science. It is organized by the National Research and Development Institute for Textiles and Leather - Leather and Footwear Research Institute Division (INCDTP-ICPI), Bucharest, Romania, and will take place online on October 30-31, 2024. ICAMS 2024 aims to highlight recent developments in material science and technology, covering a wide range of topics from theoretical research and experimental approaches to industrial practice. The conference seeks to gather eminent scientists, technologists, and young researchers from various disciplines around the world to provide a common platform for discussing their achievements and the newest directions of research. Scientific Program Features: Plenary sessions Invited talks Oral presentations Conference Topics: Advanced Materials and Nanomaterials Biomaterials and Biotechnologies Innovative Systems, Technologies, and Quality Management Ecological Processes for a Circular and Neutral Economy Creative Industries and Cultural Heritage Education and Digitalization Submission of papers via the Editorial Manager Conference date, place30-31 October 2024, onlineConference OrganizerThe National Research and Development Institute for Textiles and Leather (INCDTP) – Leather and Footwear Research Institute Division (ICPI)Article Processing Charge (APC)The conference participation fee is 150 euro, with a discounted fee of 75 euro for PhD students, and covers participation with two full papers as first author. After September 30th¬, the fees are 200 and 100 euro, respectively.Editor-in-ChiefLaurenția Alexandrescu, INCDTP-ICPI, RomaniaManaging EditorDana Gurău, INCDTP-ICPI, Romania Editorial Policy Scientific Committee Paper Template Organizing Committee Instructions for authors Guidelines for reviewers ICAMS 2024 Final Program ABSTRACTING & INDEXING Baidu ScholarBayerische StaatsbibliothekBDSBoDBowker Book DataCiandoCNKI Scholar (China National Knowledge Infrastructure)DimensionsEBSCOExLibrisGoogle BooksGoogle ScholarNavigaReadCubeSemantic Scholar TDOne (TDNet)WorldCat (OCLC)X-MOL